Study of the Oxidative Status and Some Cytokines in Children with Giardiasis - Abdullah, Salam Khalid Mutlag (American Journal of Biodiversity, 2025)
Acute and chronic diarrheal illnesses are frequently caused by Giardia lamblia in people all over the world. Studying the variations in interleukins (ILs) in giardiosis patients is especially important because ILs directly impact an immune response. In order to expose the oxidative state and certain cytokines in children with giardiasis, the current study was conducted. To find out if the child has a G. lamblia infection, a general stool investigation was performed. The parasitology unit saw 150 youngsters under the age of 15 between May and August of 2024. Abdominal discomfort and diarrhea plagued the chosen children. The results showed 17(13.1%) samples were found positive for giardiasis, while 113(86.9%) samples were negative. The gender of patients showed non-significant (P≤0.05) differences. The percentage of infected male patients at (52.9%) while, the percentage of female patients at (47.1%). The age of patients showed significant (P≤0.05) differences. 1-3-year group showed high percentage of infected patients at (52.9%) while, the percentage was showed in 10-12 year which reached 5.9%. The results found that the concentration of IL-2 (34.19± 3.88), IL-4 (19.53± 1.73) and IL-10 (16.52± 0.36) showed significant (P≤0.05) elevated between G. lamblia patients compared to the control group (12.04± 1.47; 8.91± 1.61; 9.04± 0.42 respectively). We conclude that pro-inflammatory and anti-inflammatory interleukins play a significant role in Giardia lamblia infection because the levels of interleukins (IL-2, IL-4, and IL10) were elevated in the infected patient relative to healthy individuals.